Interprofessional education in geriatric medicine: towards best practice. A controlled before–after study of medical and nursing students. Issue 1 (20th January 2020) - Thompson, Sanja; Metcalfe, Kiloran; Boncey, Katy; Merriman, Clair; Flynn, Lorna Catherine; Alg, Gaggandeep Singh; Bothwell, Harriet; Forde-Johnston, Carol; Puffett, Elizabeth; Hardy, Caroline; Wright, Liz; Beale, James
Abstract : Objectives: To investigate nursing and medical students' readiness for interprofessional learning before and after implementing geriatric interprofessional education (IPE), based on problem-based learning (PBL) case scenarios. To define the optimal number of geriatric IPE sessions, the size and the ratio of participants from each profession in the learner groups, the outcomes related to the Kirkpatrick four-level typology of learning evaluation, students' concerns about joint learning and impact of geriatric IPE on these concerns. The study looked at the perception of roles and expertise of the 'other' profession in interprofessional teams, and students' choice of topics for future sessions. Students' expectations, experience, learning points and the influence on the understanding of IP collaboration, as well as their readiness to participate in such education again were investigated. Design: A controlled before–after study (2014/2015, 2015/2016) with data collected immediately before and after the intervention period. Study includes additional comparison of the results from the intervention with a control group of students. Outcomes were determined with a validated 'Readiness for Interprofessional Learning' questionnaire, to which we added questions with free comments, combining quantitative and qualitative research methods. The teaching sessions were facilitated by experienced practitioners/educators, so each group had both, a clinician (either geratology consultant or registrar) and a senior nurse. Participants: 300 medical, 150 nursing students. Setting: Tertiary care university teaching hospital. Results: Analysis of the returned forms in the intervention group had shown that nursing students scored higher on teamwork and collaboration post-IPE (M=40.78, SD=4.05) than pre-IPE (M=34.59, SD=10.36)—statistically significant. On negative professional identity, they scored lower post-IPE (M=7.21, SD=4.2) than pre-IPE (M=8.46, SD=4.1)—statistically significant. The higher score on positive professional identity post-IPE (M=16.43, SD=2.76) than pre-IPE (M=14.32, SD=4.59) was also statistically significant. Likewise, the lower score on roles and responsibilities post-IPE (M=5.41, SD=1.63) than pre-IPE (M=6.84, SD=2.75). Medical students scored higher on teamwork and collaboration post-IPE (M=36.66, SD=5.1) than pre-IPE (M=32.68, SD=7.4)—statistically significant. Higher positive professional identity post-IPE (M=14.3, SD=3.2) than pre-IPE (M=13.1, SD=4.31)—statistically significant. The lower negative professional identity post-IPE (M=7.6, SD=3.17) than pre-IPE (M=8.36, SD=2.91) was not statistically significant. Nor was the post-IPE difference over roles and responsibilities (M=7.4, SD=1.85), pre-IPE (M=7.85, SD=2.1). In the control group, medical students scored higher for teamwork and collaboration post-IPE (M=36.07, SD=3.8) than pre-IPE (M=33.95, SD=3.37)—statistically significant, same for positive professional identity post-IPE (M=13.74, SD=2.64), pre-IPE (M=12.8, SD=2.29), while negative professional identity post-IPE (M=8.48, SD=2.52), pre-IPE (M=9, SD=2.07), and roles and responsibilities post-IPE (M=7.89, SD=1.69), pre-IPE (M=7.91, SD=1.51) shown no statistically significant differences. Student concerns, enhanced understanding of collaboration and readiness for future joint work were addressed, but not understanding of roles. Conclusions: Educators with nursing and medical backgrounds delivered geriatric IPE through case-based PBL. The optimal learner group size was determined. The equal numbers of participants from each profession for successful IPE are not necessary. The IPE delivered by clinicians and senior nurses had an overall positive impact on all participants, but more markedly on nursing students. Surprisingly, it had the same impact on medical students regardless if it was delivered to the mixed groups with nursing students, or to medical students alone. Teaching successfully addressed students' concerns about joint learning and communication and ethics were most commonly suggested topics for the future.